PERILAKU POLITIK PEMILIH PEMULA DALAM PEMILIHAN PRESIDEN 2019 DI KECAMATAN UNGAR KABUPATEN KARIMUN PROVINSI KEPULAUAN RIAU - Nur, Ricafinalia; Erlinda, Sri; Zahirman, Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study is entitled"Novice Voter Political Behavior In The 2019 Presidential Election In Ungar District, Karimun Regency".The formulation of the problem of this research how is itnovice voter political behavior in the 2019 presidential election in Ungar District, Karimun Regency, seen from sociological approach, psychological approach and rational approach.The purpose of this study is to analyze and find out novice voter political behavior in the 2019 presidential election in Ungar District, Karimun Regency, seen from sociological approach, psychological approach and rational approach. The population in this study were all first-time voters in Ungar District, totaling 511 people.Sample in this study amounted to 84 respondents. Data collection techniques in this study were interviews, questionnaires and documentation.Data analysis techniques in this study used quantitative and qualitative descriptive methods (mix methoad). The conclusion in this study is novice voters in determining their political choices look more at the emotional closeness to the party, its origins, issues that develop and background owned by the candidate they chose. In other words psychological approach factors have a great influence on the behavior of novice voters in Ungar District in making their political choices in the 2019 presidential election.KeyWords: Political Behavior, Newbie Voter, Presidential Election